Motor Cortex Reorganization in Limb Amputation: A Systematic Review of TMS Motor Mapping Studies - Gunduz, Muhammed Enes; Pinto, Camila Bonin; Saleh Velez, Faddi Ghassan; Duarte, Dante; Pacheco-Barrios, Kevin; Lopes, Fernanda; Fregni, Felipe (Frontiers in Neuroscience, 2020)
Purpose: The purpose of this mini review is to evaluate motor cortex reorganization in amputees as indexed by transcranial magnetic stimulation (TMS) cortical mapping and its relationship with phantom limb pain (PLP). Methods: Pubmed database were searched. Three independent researchers screened the relevant articles, and the data of motor output maps, including the number of effective stimulation sites, center of gravity (CoG) shift and their clinical correlations were extracted. We calculated a pooled CoG shift for motor cortex TMS mapping. Results: The search yielded 468 articles, 11 were included. 3 studies performed correlation between the cortical changes and PLP intensity, and only one study compared cortical mapping changes between amputees with pain and without pain. Results showed (i) enlarged excitable area and a shift of CoG of neighboring areas towards the deafferented limb area; (ii) no correlation between motor cortex reorganization and level of pain and (iii) greater larger cortical reorganization in patients with PLP compared to amputation without pain. Conclusion: Our review supports the evidence for cortical reorganization in the affected hemisphere following an amputation. The motor cortex reorganization could be a potential clinical target for prevention and treatment response of PLP.